Enhancing the Accuracy of Use Interpretation: The Discovery of a New Wear Formation with the Complementary Methods of Experimental Archaeology and Use-Wear Analysis - Amber Roy (EXARC, 2020)
Experimental archaeology and use-wear analysis are methods used together to understand aspects of an object’s life, such as manufacture and use. This paper demonstrates the benefits of analysing use-wear through experiments. It presents the results of experiments which were carried out to test the use of battle-axes and axe-hammers. Most notably, the paper presents the new discovery of a previously unknown use-wear formation, the ‘three-group-arrangement’. This is a formation of wear on bladed implements which forms in the early stages of use – in contact with wood using chopping motions. Its discovery was only possible through the analysis of wear development throughout experiments. This use-wear formation was analysed on stone battle-axes and axe-hammers from the northern British Isles, c. 2200 - 1500 BC and allowed an interpretation of their use which was not previously possible for several artefacts in this assemblage. The discovery of this wear pattern significantly adds to the knowledge of use-wear formation on bladed and perforated, ground and polished stone implements which have previously been overlooked. It allows the previously unfeasible interpretation of less developed wear, formed during the early stages of use in contact with wood. The results demonstrate the importance of analysing the changing use-wear formations throughout experiments to understand the formation of use-wear patterns on implements in the archaeological record.